A COMPARATIVE STUDY OF THE CATEGORY OF VERB IN ENGLISH AND UZBEK LANGUAGES - Sotvoldiyev Sohibjon Madaminovich, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
This thesis presents a comparative analysis of the category of the verb in the English  and  Uzbek  languages.  The  study  examines  the  expression  of  grammatical meanings  in  both  languages,  accounting  for  their  typological  distinctions.  English verbs are primarily characterized by analytical structures, whereas Uzbek verbs rely on agglutinative forms. The research is grounded in the theoretical frameworks of Otto Jespersen and V.V. Vinogradov, whose approaches to verbal categories provide a solid foundation  for  this  comparison.  The  thesis  identifies  both  universal  (shared)  and language-specific features of the verbal systems in English and Uzbek.